Mothers Knowledge about Nutritional Status of their Children in Primary Health Centers at Baghdad City - Samar Hussein Kareem (Institute of Medico-legal Publications Pvt Ltd, 2021)
Nutrition is a critical feature of a lifetime and plays an important role in the growth and development of ahealthy child free from illness and disability. The objective analysis is to assess the mother’s awareness ofthe nutritional status of her children and to evaluate her relationship with socio-demographic characteristicsin Baghdad District (Karkh and Rasafa area).Methodology: Methodology: The Descriptive Study was planned to assess mothers with informationconcerning the nutritional status of their children from January 2020 to November 2020 in the Karkh andRasafa areas of Baghdad Region.The sample form is intended for 100 volunteer mothers who have been chosen randomly from the PrimaryHealth Center in Bagdad City to participate in the study. The study included four health centers dividedbetween the Karkh and Rasafa regions of Bagdad, and the number of samples in each center was (25)participating mothers.Results: The findings of the study have been verified by the use of the fisher-test and ANOVA to assessmothers’ knowledge of the nutritional status of their children of high significance between mothers’knowledge and age, occupation status, number of children in the family at (p-value < 0.01), while the levelof schooling, monthly income and knowledge sources have shown that there is no relevance to this.